PENGARUH KOMPETENSI DAN ETOS KERJA PEGAWAI TERHADAP KUALITAS PELAYANAN DI KANTOR URUSAN AGAMA KECAMATAN KEMPAS - Rukmana Sari, Intan; Arifin, Zainal; Bindas, Asniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and describe in depth how employee competence and work ethic influence service quality at the Office of Religious Affairs (Kantor Urusan Agama/KUA) of Kempas District. Employing a qualitative approach with a case study design, the research involved the Head of the KUA, implementing staff members, and service users as key informants. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate that KUA Kempas faces complex service dynamics, characterized by fluctuations in marriage cases in the post-pandemic period and high demands for out-of-office services. The findings indicate, that employee competence (technical and interpersonal knowledge) and employee work ethic (discipline and commitment) are proven to have a positive and significant effect, both partially and simultaneously, on improving service quality, particularly in the aspects of Reliability and Responsiveness. The main conclusion emphasizes that excellent service quality at the KUA emerges from a harmonious synergy between adequate technical capability (competence) and a professional willingness to work (work ethic). Therefore, it is recommended that the KUA prioritize technical training and the strengthening of work morale to ensure adaptive services and public satisfaction.